Actualization of Anti-Corruption Values in the Local Wisdom of the Bali Community - Ni Luh Gede Hadriani; Gede Yoga Satrya Wibawa (Sociological Jurisprudence Journal, 2022)
Presently, corruption in Indonesia is very worrying, although various actions have been taken, it turns out that corruption tends to exist and continues to increase both in quantity and quality. The severity of the disease of corruption that afflicts our nation cannot be left alone; we must find a way out, no matter how hard and difficult the terrain is. At least this downturn still leaves a blessing, giving us the opportunity to reflect, think clearly about the corruption problem we are facing. One way to develop the value of anti-corruption values ​​is; honesty, discipline, and responsibility are with; 1) explore, study, and understand the potential for anti-corruption values ​​contained in local wisdom and 2) actualize these anti-corruption values ​​in people's lives. Balinese people have various forms of Local Wisdom in fostering non-corrupt behavior. The potential of Local Wisdom is related to the values ​​of: Honesty Value, Caring Value, Independence Value, Discipline Value, Responsibility Value, such as believing in the law of karma phala, The existence of paiketan alliances in traditional villages. Value of Hard Work, Value of Courage, and Value of Justice. The steps that need to be taken in actualizing anti-corruption values ​​in the life of the Hindu community in Bali are by doing Dharma Discourse, Dharma Tula, Dharma Gita and Dharma Sedana. With the target of actualization are Children, Young Generation and the community.